History matters in making Lahore sustainable - Imran, Muhammad; Mehmood, Abid; Cheema, Abdur Rehman (International Planning History Society Proceedings, 2018)
Lahore, the second-largest city of Pakistan, is facing sharp population growth and economic development coupled with increased motorisation and a deteriorating urban environment. This is due to a long history of investment into roads and low-density suburban housing development in Lahore which increases motorisation. This paper provides a historical overview of urban planning in Lahore by shedding light on the Mughal and the British period of development followed by the post-independence planning paradigm in the city. This paper examines the contradictions and uncertainties that have characterised urban planning in Lahore in the pre and post-independence period by using a sustainable city and sustainable transport literature. The analysis shows that Lahore traditionally attracted investment in the high-quality roads infrastructure (flyovers, underpasses and a ring road) and recently in the country first ever Bus Rapid Transit (BRT) system (2013) and Metro Train project (2018) in the city. The paper argues that the Lahore BRT and Metro train projects can provide a window of opportunity to redefine transport and land use issues and offer a transit-oriented development (TOD) solutions in Lahore.